Digital agriculture profile in Salvador - Gómez Restrepo, Maria Camila (International Center for Tropical Agriculture, 2020)
The initial diagnostic of this product resulted from a visit to El Salvador. The current landscape of digital agriculture was key to identify and prioritize D-CSA challenges to maximize impact on the improvement of agro-systems in El Salvador.